Sleep quality and academic performance among nursing student in USM and UiTM - Mohamad, Normah (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2022)
Sleep is a repetitive and reversible neurobehavioral state characterized by relative perceptual detachment and insensibility to the external stimuli. A cross-sectional study has been conducted to determine mean score sleep quality among diploma and degree nursing students in USM and UiTM. This study also examined the difference between sleep quality and academic performance among diploma and degree nursing students in USM and UiTM. Fisher Exact Test was used to determine the association between sleep quality and academic performance among nursing students in USM and UiTM. A total of 298 undergraduate nursing students, 196 nursing students from USM and 102 nursing students from UiTM were recruited through simple random sampling method. Data were collected from April 2022 until May 2022 using google form and analysed using SPSS version 26.0 for a window. The result in this study revealed that majority nursing students in USM and UiTM had poor sleep quality (p = 0.534, p = 0.614). The difference showed that there is no significant association between sleep quality and academic performance among nursing students in USM and UiTM (p= 1.000). In conclusion, a good sleep quality needed for nurses to ensure deliver the best nursing care.